Tecnologias educativas em prevenção de infecções sexualmente transmissíveis e saúde mental - Siqueira, Laís Quevedo (2023)
Introduction: Mental health problems and the use of psychoactive substances are issues that are related to the greater probability of contracting Sexually Transmitted Infections. To this end, it is necessary to map the technologies aimed at assisting people with such conditions. Objective: To map, in original studies, educational health technologies aimed at people with mental health problems and the use of psychoactive substances for the prevention of Sexually Transmitted Infections. Method: this is an integrative literature review. To search for articles in the LILACS database, the search strategies used were “Mental illness” AND “Health education” AND “Sexually Transmitted Infections”. In the PubMed and Scopus databases, the terms were used: “Mental disorders” AND “Health education” AND “Sexually transmitted disease”. The searches were carried out between September and October 2022. Results: 120 articles make up the corpus of the analysis. The most evident target audience in the studies were people who use psychoactive substances and injecting drug users, with predominance in the application of questionnaires, in addition to educational interventions for risk reduction, prevention and psychoeducation. The most discussed topics in the studies were related to behavior in general, harm and risk reduction, HIV prevention, in addition to information on HIV/AIDS, Sexually Transmitted Infections, hepatitis, condom use. Conclusion: As a contribution of the study to the health area, especially Occupational Therapy and Nursing, which develop groups and workshops, it was possible to learn about the various educational technologies and subjects addressed in this context, with the aim of qualifying communication with people with mental health problem and who use psychoactive substances, offering support for the management of these situations by the entire team. As a future perspective, due to the scarcity of validated educational technologies for interventions with this public, it is proposed the development and validation of guides as tools for this purpose, with the aim of contributing more directly to this public.